Euthanasia Dalam Perspektif Hukum Pidana Indonesia - Habibiellah Huda; Ismansyah, Ismansyah; Edita Elda (Universitas Ekasakti, 2024)
The increasing development of technology in the health sector has led to many new things that can be done, one of which is euthanasia which is often debated in Indonesia and around the world. Euthanasia comes from the words